Isolation of a Functional Gene Encoding Homologous Lysophospholipase from Indonesian Indigenous Bacillus halodurans CM1 - SHANNI FERNANDA; ABINAWANTO ABINAWANTO; IS HELIANTI (Microbiology Indonesia, 2019)
Lipase is a biocatalyst widely used in industry, for example detergent, pharmaceutical, food, or oil purification. One of the most widely lipase used for oil purification is lysophospholipase. As much as 50% of industrial enzyme needs are supplied from microorganisms. However, enzyme productivity from wild type microbial strain is usually limited and not applicable in industry, so that genetic engineering is necessary. Cloning gene encoding for lysophospholipase from Aspergillus niger and Cryptococcus neoformans have been conducted, but has never been conducted from alkalothermophilic bacteria, such as Bacillus halodurans. Bacillus halodurans CM1 is an alkalothermophilic bacterial strain isolated previously that has many industrially potential enzymes. This study aimed to isolate one of the gene encoding lipase from Bacillus halodurans CM1 and cloned into Escherichia coli DH5Î± using the pGEM-T easy vector. The gene fragment encoding lysophospholipase obtained with size 783 base pairs and had 100% similarity with gene encoding lysophospholipase from Bacillus halodurans C-125 (No access GenBank: BA000004.3). E. coli harbouring the recombinant plasmid with the gene also showed activity on trybutiryn medium compared to negative control.